Research of Mechanical Interface Control Model for Aircraft Digital Mock up. Issue 1 (July 2021) - Jian, Xu; Xinai, Zhang; Hao, Su
Abstract: Mechanical interface design is used to clarify the design division and interface of all parties, and is one of the important tasks of aircraft design. The mechanical interface control model is a digital representation of the mechanical interface characteristics between one aircraft system (including structure) and another. It is a model carrier for mechanical interface design collaboration. This article introduces the definition and classification of the mechanical interface control model of the aircraft digital mock up, focuses on the general design process, requirements, application and management of the mechanical interface control model, it provides relevant reference and help for the design and management of the mechanical interface of the aircraft digital mock up.